Comparison of Teacher and School Managers' Assignment Policies Between South Korea, Singapore, Japan, Finland and Turkey - Aksoy, Mahmut; Karagozoglu, Ahmet Alper (Univ San Ignacio Loyola, 2021)
In this study, South Korea, Singapore, Japan, Finland and Turkey Countries teachers and school administrators were compared in terms of assignment policies. In this research, a holistic multiple state pattern, which is one of the qualitative research types, was used. The reason for using this method has been examined in accordance with the problem situation of these countries and then compared with each other. The appointment policies of teachers and school administrators should be evaluated along with other processes. South Korea, Singapore, Japan, Finland countries excelled in PISA 2003, 2006, 2009 and 2012 exams. The selection of qualified teachers and school administrators plays an important role in this success of these countries. While choosing candidates for education faculties in these countries, exams measure their teaching skills via central exams. In the process of assigning teachers, central exams are conducted, but institutions again conduct exams that measure their teaching skills. Teaching appeal is a profession in these countries. Because in these countries, teaching has all the features such as respectability, high status, job guarantee and high salary. Teacher salaries in these countries are above the average of OECD countries. In addition, great importance is attached to the in-service training of school administrators and teachers in these countries. The salaries of teachers in Turkey is below the average of OECD countries.
Keywords: South Korea; Finland; Singapore; Japan; Turkey; Teachers and School Administrators Assignment Policies